Continuous assembly of supramolecular polyamine–phosphate networks on surfaces: preparation and permeability properties of nanofilms. Issue 7 (24th January 2019) - Agazzi, Maximiliano L.; Herrera, Santiago E.; Cortez, M. Lorena; Marmisollé, Waldemar A.; von Bilderling, Catalina; Pietrasanta, Lía I.; Azzaroni, Omar
Abstract : Polyamine-phosphate networks represent a powerful "nanoarchitectonic" tool to create new functional materials with molecular-level control. Abstract : Supramolecular self-assembly of molecular building blocks represents a powerful "nanoarchitectonic" tool to create new functional materials with molecular-level feature control. Here, we propose a simple method to create tunable phosphate/polyamine-based films on surfaces by successive assembly of poly(allylamine hydrochloride) (PAH)/phosphate anions (Pi) supramolecular networks. The growth of the films showed a great linearity and regularity with the number of steps. The coating thickness can be easily modulated by the bulk concentration of PAH and the deposition cycles. The PAH/Pi networks showed chemical stability between pH 4 and 10. The transport properties of the surface assemblies formed from different deposition cycles were evaluated electrochemically by using different redox probes in aqueous solution. The results revealed that either highly permeable films or efficient anion transport selectivity can be created by simply varying the concentration of PAH. This experimental evidence indicates that this new strategy of supramolecular self-assembly can be useful for the rational construction of single polyelectrolyte nanoarchitectures with multiple functionalities.